2017
DOI: 10.1111/add.13800
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported substance use in Iraq: findings from the Iraqi National Household Survey of Alcohol and Drug Use, 2014

Abstract: Psychoactive drug use is generally low in Iraq, tobacco being highest at an estimated 23.2%. Iraqi women report significantly less substance use than Iraqi men, which may be related to cultural gender norms. Discrepancy between self-report and 'knowing someone who uses a substance' suggests under-reporting in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 23 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…Studies from Egypt showed a high rate of 8.8 to 12.3% of tramadol use among high school and university students [106,109]. Self‐reported prevalence of knowing someone who currently uses tramadol was 2.4% in the Iraqi general population [110]. In the United States, due to a significant increase in tramadol abuse and overdose, tramadol was added to scheduled medications in 2014 [111].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Egypt showed a high rate of 8.8 to 12.3% of tramadol use among high school and university students [106,109]. Self‐reported prevalence of knowing someone who currently uses tramadol was 2.4% in the Iraqi general population [110]. In the United States, due to a significant increase in tramadol abuse and overdose, tramadol was added to scheduled medications in 2014 [111].…”
Section: Discussionmentioning
confidence: 99%
“…This represents an increase of 0.4% since 2006 (4). In Iraq (including Kurdistan Region), according to the final report of the Iraq National Household Survey on Alcohol and Drug Use (INHSAD), the lifetime prevalence rates of tobacco use, alcohol consumption, nonmedical use of prescription drugs, and use of illicit drugs were 28.8%, 8.1%, 2.9%, and 0.7%, respectively (5). Another report, from the Iraqi Community Epidemiology Work Group, suggests that there has been increased use of alcohol and prescription and illicit drugs in Iraq since 2009, especially among adolescents (6).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the geographic location of Iraq is another factor that makes Iraq vulnerable to substance use, this is because of the long and porous border between Iraq and Iran, as Iran faces an increasing and very serious problem in substance use [ 6 ]. According to the more recent report, the prevalence of lifetime uses of (Alcohol, Licit or Illicit Drugs) in Iraq (Including Kurdistan region) was approximately 10.3% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%